Роль біопродуктивності лісів Карпатського національного природного парку у формуванні вуглецедепонувального потенціалу регіону - Бокоч, В.В.; Василишин, Р.Д. (Економіка природокористування і охорони довкілля, 2013)
Визначено обсяги фітомаси й депонованого вуглецю в лісах Карпатського НПП та їх внесок у формування вуглецевого бюджету регіону. The amount of phytomass and deposited carbon in forests of the Carpathian NNP and their contribution to the carbon budget of the region have been defined. Adapted and implemented methodology for calculating bioproductivity of tree stands by components of phytomass and depositing carbon was to find out their multifactorial dependencies on mensurational characteristics of stands, which are specified in the State forest inventory data. As the depending variable in modeling the dynamics of phytomass components of stands conversion factor was used (ratio of the mass of phytomass fraction to volume of trunk over bark).